The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10461-016-1638-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV Care Engagement, Antiretroviral Medication Adherence, and Viral Suppression Among People Living with HIV Infection in St. Petersburg, Russia

Abstract: Over 1 million HIV infections have been diagnosed in Russia, and HIV care uptake and viral suppression are very low. 241 HIV-positive individuals in St. Petersburg were enrolled through social networks, provided blood for viral load testing, and completed measures of medication-taking adherence, readiness, and self-efficacy; psychosocial well-being; and substance use. Outcomes included attending an HIV care appointment in the past 6 months, >90% ART adherence, and undetectable viral load. 26% of participants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 41 publications
2
22
0
2
Order By: Relevance
“…Findings specifically support those of earlier studies that identified alcohol use as a risk factor for lower engagement in HIV care, 2123,27,60 treatment with ART 24,25,27 and viral suppression. 26,27 Moreover, this study newly demonstrated a dose-dependent association between alcohol use and three HIV care continuum outcomes such that PLWH reporting alcohol use at medium, high, and very high levels had progressively lower likelihood of all care continuum outcomes relative to patients who reported non-drinking. Further, in secondary analyses, diagnosis for AUD was associated with lower likelihood of treatment with ART and viral suppression.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings specifically support those of earlier studies that identified alcohol use as a risk factor for lower engagement in HIV care, 2123,27,60 treatment with ART 24,25,27 and viral suppression. 26,27 Moreover, this study newly demonstrated a dose-dependent association between alcohol use and three HIV care continuum outcomes such that PLWH reporting alcohol use at medium, high, and very high levels had progressively lower likelihood of all care continuum outcomes relative to patients who reported non-drinking. Further, in secondary analyses, diagnosis for AUD was associated with lower likelihood of treatment with ART and viral suppression.…”
Section: Discussionsupporting
confidence: 85%
“…However, previous studies offer limited information on the influence of alcohol use on HIV care continuum targets in the U.S. for several reasons. First, most studies have been conducted within samples of PLWH living outside of the U.S. 17,24,25,27 or in recruited samples with limited generalizability. 18,30,31 Second, existing studies do not assess multiple components of the HIV care continuum in a single sample of PLWH, limiting understanding of the effect of alcohol use across care targets.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress, it seems unlikely that many regions and countries will meet the 2020 target. knowledge of status in previously reported estimates was thought to be high as a result of extensive testing, but linkage to treatment remains a challenge [32,33]. In the Middle East and North Africa, persistently low estimates of knowledge of HIV status and treatment access point to the role of stigma and discrimination in service delivery as possible causes [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Standard presentations of the HIV continuum of care at the national level are likely to mask variations that exist in and between key subpopulations. National descriptions of the continuum of care stratified by key populations have been undertaken in the USA , the UK , Belgium , Canada , Denmark , France , Georgia , Greece and Russia and international comparisons have been carried out . However, no baseline continuum of HIV care data are available for key populations for the whole European and Central Asian region.…”
Section: Introductionmentioning
confidence: 99%